2014
DOI: 10.1128/aac.00051-14
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Micafungin Monotherapy for Candidemia and Deep-Seated Candidiasis in Adults with Cancer

Abstract: The response rate among 58 patients with cancer and candidemia or deep-seated candidiasis treated with micafungin monotherapy was 81%. Intensive care unit (ICU) stay, concomitant nonfungal infections, and acute kidney injury were significantly associated with the 30-day crude mortality rate. Severe neutropenia was an independent predictor of micafungin failure. The efficacy and safety of micafungin in cancer patients with invasive candidiasis were comparable to those reported for patients without malignancy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…In patients with invasive fungal infections the recommended length of therapy is 14 days after the first negative blood culture [ 9 , 24 ], which is in line with the observed median length of treatment of 12–14 days in this study. The overall response rates in this study are comparable to those found in other performed studies [ 11 , 32 ]. The overall response rate of micafungin is comparable to that of anidulafungin.…”
Section: Discussionsupporting
confidence: 90%
“…In patients with invasive fungal infections the recommended length of therapy is 14 days after the first negative blood culture [ 9 , 24 ], which is in line with the observed median length of treatment of 12–14 days in this study. The overall response rates in this study are comparable to those found in other performed studies [ 11 , 32 ]. The overall response rate of micafungin is comparable to that of anidulafungin.…”
Section: Discussionsupporting
confidence: 90%
“…Candidemia and IFIs are major complications in patients with HMs who develop prolonged and severe neutropenia. Additionally, IFIs are difficult to diagnose in these severely immunocompromised patients [88][89][90][91]. In patients with MM prior to the introduction of novel therapies, IFIs were encountered in patients treated with traditional intensive cytotoxic chemotherapeutic regimens and mortality rates due to IFIs were reaching 60% [91].…”
Section: Fungal Infections In MMmentioning
confidence: 99%
“…Over the past two decades, the spectrum of Candida species infections has shifted to non-albicans species, which frequently exhibit decreased susceptibility to fluconazole [89]. Empirical antifungal agents are recommended in patients with HMs having neutropenia and persistent or recurrent fever despite appropriate antibiotic therapy [88].…”
Section: Fungal Infections In MMmentioning
confidence: 99%
See 1 more Smart Citation
“…Echinocandins, which inhibit cell wall glucan synthesis, were a major development in antifungal therapy. In addition to the enhanced spectrum of echinocandins over that of triazole therapy, studies have demonstrated the efficacy of echinocandins for the prevention and treatment of invasive candidiasis (3,(6)(7)(8)(9)(10)(11)(12). Echinocandins also are associated with a very low incidence of adverse effects and have an excellent safety profile.…”
mentioning
confidence: 99%